Finite Element Analysis of the Temperature Field of an Emergency Brake and Study of its Thermal Properties - Wen, H.; Yang, F.; Lv, W.Q.; Chen, Y.X.; Wang, Q.W. (Проблемы прочности, 2015)
For simulation of typical operating conditions of an emergency brake, analyze the theoretical heat energy of single emergency braking. The formula of the maximum temperature of a contact point was derived from the theory of friction heat conduction during braking. The finite element model of the disc brake temperature field was constructed with ANSYS/LS-DYNA software. The effect of brake safety factor and different thermal properties on the temperature field is analyzed, indicating that the temperature distribution of ductile iron brake friction pairs is superior to the steel brake ones. The results and analysis provide certain indications of the design and applicability of an emergency brake. Для моделирования типичных условий эксплуатации аварийного тормоза проанализирована теоретическая тепловая энергия одного аварийного торможения. Выведена формула максимальной температуры контактной точки на основании теории теплопроводности трения при торможении. Конечноэлементная модель температурного поля дискового тормоза была построена с использованием программного пакета ANSYS/LS-DYNA. Проанализировано влияние запаса прочности тормaза и различных тепловых свойств на температурное поле. Результаты показали, что распределение температур в парах трения тормоза из чугуна с шаровидным графитом более равномерно, чем в парах трения стального тормоза. Полученные результаты и выполненный анализ позволяют дать некоторые рекомендации относительно конструкции и применения аварийного тормоза.